A STUDY ON TEASING UTTERANCES IN COMEDY MOVIE MANUSCRIPTS: SOCIO-PRAGMATICS APPROACH - PUTRANTI , OKTIVIA WIDI (2007)
This research paper studies about teasing utterances in comedy movie manuscripts. The objects used to be analyzed are teasing utterances in the form of word, phrase, clause and sentence. The writer takes the data from comedy movie manuscripts entitled American Shaolin and White Chicks. In collecting data, the writer uses observation non-participant method by selecting the teasing utterances which can be found in those comedy movie manuscripts. This research is aimed at describing forms, finding out the speaker's intention and identifying the reason of employing teasing utterances. To describe the form, the writer uses grammatical form. To analyze the speaker's intention, the writer uses pragmatics analysis, especially locutionary, illocutionary and perlocutionary. To clarifying the reason, the writer employs SPEAKING Hymes Formula. Having analyzed the data, the writer finds that the form patterns of teasing utterances are word, noun phrase, prepositional phrase, declarative sentence, interrogative sentence and exclamatory sentence. The speaker's intentions are mocking, threatening, asserting, teasing, answering and expressing surprise. The reasons of the speaker are showing mocking, showing annoyance, showing teasing, showing surprise, showing arrogance, showing dislike, showing fear, and showing anger.